ADHD symptoms, the current symptom scale, and exploratory structural equation modeling: A psychometric study. (April 2021) - Gomez, Rapson; Stavropoulos, Vasileios; Zarate, Daniel; Griffiths, Mark
Abstract: The aim of the study was to use exploratory structural equation modelling (ESEM) to investigate support for an ADHD factor model with group factors for inattention (IA), hyperactivity (HY), and impulsivity (IM), as proposed in in ICD-10. A total of 202 adults (121 females and 81 males), aged between 18 and 35 years, from the general community, completed the Current Symptoms Scale (CSS). The results for the model showed good global fit, good convergent and divergent validities. However, the IA and IM factors, but not the HY factor, were clearly defined and demonstrated acceptable reliabilities. Taken together, these finding indicate that a revised ESEM model without the HY factor (i.e. with only the IA and IM symptoms) is an appropriate structure for modeling adult ratings of the ADHD behaviors described in the CSS. The taxonomic, theoretical and clinical implications of the findings for ADHD in general are discussed.